Intensive disc-reverberation mapping of Fairall 9: first year of Swift and LCO monitoring. Issue 4 (21st September 2020) - Hernández Santisteban, J V; Edelson, R; Horne, K; Gelbord, J M; Barth, A J; Cackett, E M; Goad, M R; Netzer, H; Starkey, D; Uttley, P; Brandt, W N; Korista, K; et al.
ABSTRACT: We present results of time-series analysis of the first year of the Fairall 9 intensive disc-reverberation campaign. We used Swift and the Las Cumbres Observatory global telescope network to continuously monitor Fairall 9 from X-rays to near-infrared at a daily to subdaily cadence. The cross-correlation function between bands provides evidence for a lag spectrum consistent with the τ  ∝  λ 4/3 scaling expected for an optically thick, geometrically thin blackbody accretion disc. Decomposing the flux into constant and variable components, the variable component's spectral energy distribution is slightly steeper than the standard accretion disc prediction. We find evidence at the Balmer edge in both the lag and flux spectra for an additional bound-free continuum contribution that may arise from reprocessing in the broad-line region. The inferred driving light curve suggests two distinct components, a rapidly variable (<4 d) component arising from X-ray reprocessing, and a more slowly varying (>100 d) component with an opposite lag to the reverberation signal.